Economic Evaluation of Adolescent Vaccination with Serogroup ACWY and C Meningococcal Vaccines in Germany - Sebastian Gruhn; Manuel Batram; Moritz Wick; Edith Langevin; Stefan Scholz; Wolfgang Greiner; Oliver Damm (Infectious Diseases and Therapy)
Abstract Introduction Invasive meningococcal disease (IMD) is a rare but serious condition caused by Neisseria meningitidis, with rising cases of serogroups W and Y in Germany. Currently, routine vaccination in Germany includes MenC vaccination in toddlers, and as of early 2024, MenB vaccination has been recommended in infancy. MenACWY vaccination, however, is currently only recommended for high-risk individuals. This study evaluates the potential public health impact and cost-effectiveness of introducing routine adolescent MenACWY or MenC vaccination in Germany. Methods This study presents a health economic evaluation based on a previously published dynamic transmission model, which simulates the introduction of MenACWY vaccination in adolescents in Germany. The evaluation incorporates costs and quality-adjusted life years (QALYs), and is conducted from a societal perspective. Deterministic and probabilistic sensitivity analyses were performed to assess the robustness of the findings and to account for parameter uncertainty. Results The introduction of adolescent MenACWY vaccination was estimated to prevent 1467 IMD cases and 156 deaths by 2060, leading to a total gain of 2333 QALYs. The MenACWY vaccination strategy was associated with incremental costs of approximately €306 million, resulting in an incremental cost-effectiveness ratio (ICER) of €131,150 per QALY gained. Scenarios assuming higher levels of carriage protection reduced the ICER to as low as €76,000 per QALY. In contrast, adolescent MenC vaccination had a comparatively minor impact on IMD incidence and mortality, with ICERs exceeding €1 million per QALY. Sensitivity analyses highlighted the significant influence of assumed vaccine carriage protection and duration of protection on the ICER. Conclusions Adolescent MenACWY vaccination in Germany has the potential to reduce the incidence and mortality of IMD, particularly from serogroups W and Y. Although the cost-effectiveness of the strategy depends on several assumptions, particularly the extent of carriage protection, the ICER for MenACWY introduction appears favorable.